Development and application of assay for determining β-glucosidase activity in human saliva. Issue 1 (December 2017) - Stradwick, Lauren; Inglis, Debbie; Kelly, Jennifer; Pickering, Gary
Abstract Background β-glucosidase is an enzyme important to flavour enhancement. It hydrolyzes glucosides to release aglycones—aroma precursors that are bound to a sugar molecule—thereby making them available to contribute to the flavour of foods and beverages. While there is strong interest within the food and beverage industry to optimizing flavour through the use of exogenous and endogenous glucosidase in production, little is known regarding the possible occurrence of these enzymes within the human oral cavity. This could be an important source of flavour release and/or account for some differences between individuals in flavour perception. In the present study, we determined whether β-glucosidase is present in human saliva. First, an existing spectrophotometric assay that uses p-nitrophenyl-β-O -d -glucopyranoside as a substrate was modified and optimized for use in human saliva. The following variables were evaluated and where necessary, optimized: linearity of the assay signal, possible matrix interference, the effect of heat inactivation of the saliva, absorbance wavelength maxima, substrate saturation concentration, maximum saliva volume and the inclusion of α-cyclodextrin. The modified assay was then used to screen for β-glucosidase activity in the saliva of 20 individuals. Of the 20 samples analyzed, four were tentatively identified as containing active β-glucosidase and were further investigated. Results Significant differences (p  < 0.05) in absorbance values (A400nm ) between these saliva samples confirm low levels of β-glucosidase activity in approximately 20% of the population sampled. Conclusions Inter-individual variability exists in β-glucosidase activity within the oral cavity. The described method can be applied to rapidly assay a large population of individuals, and further elucidate the extent and significance of salivary β-glucosidase activity within the context of human flavour perception and enhancement.